Pengaruh Kandungan Protein Pakan terhadap Pertumbuhan dan Efisiensi Pakan Benih Ikan Kakap Merah (Lutjanus argentimaculatus) - Nyoman Adiasmara Giri; Ketut Suwirya; Ayu Indriani Pithasari; Muhammad Marzuqi (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The experiment was aimed to know dietary protein requirement and the effect of dietary protein levels on juvenile red snapper (Lutjanus argentimaculatus). The experiment was conducted in 18 polycarbonate tanks, with each 30 liter volume. All tanks were equipped with aeration and flow through water system to maintain good water quality. Hatchery produced juvenile red snapper of 9.4 ± 0.1 g average body weight and total length of 7.7 ± 0.4 cm was randomly selected and 10 fish was stocked in each tank. Fish were fed with experimental diets contained different levels of protein, i.e., 32, 36, 40, 44, 48, and 52%.The experiment used completely random design (CRD) in triplicates. Results showed that dietary protein levels influenced growth, feed efficiency, feed intake, body protein content, and protein retention of juvenile red snapper (p<0.05). The highest weight gain (263.7%) was found on fish fed diet with 40% protein. Based on the growth and feed efficiency data, it was concluded that dietary protein requirement for juvenile red snapper was 40%.